PENGENAAN PAJAK PENGHASILAN ATAS WARIS DAN HIBAH DALAM PENGALIHAN HAK ATAS TANAH DAN/ATAU BANGUNAN DI KOTA PADANG - Oktario, Benny; Oktarina, Neneng (Alhurriyah, 2019)
Income Tax (PPh) is one of several types of tax, which is one of the primary sources of state revenue for development, which aims to improve the welfare and prosperity of the people. Income Tax (PPh) is regulated in Government Regulation number 34 of 2016. Where in each transfer of rights carried out by the taxpayer will be subject to Income Tax, but there is a transfer of rights excluded from the imposition and collection of Income Tax as stipulated in the Director-General of Taxes Regulation Number 30 / PJ / 2009, namely the removal of reasons due to inheritance and grants to blood families in a straight line. From this income tax collection, it is necessary to know some problems that arise. The issues, namely First, how is the imposition of Income Tax on inheritance and grants in the transfer of rights to land and buildings in the City of Padang. Second, is the Constraint in imposing income tax on estate and concessions in the removal of rights to land and buildings in the City of Padang. The research method used is an empirical juridical approach, and this research is descriptive-analytical as well as collecting data in the form of document studies and field research. Based on the results of the study, it was found that: The imposition of income tax on inheritance and grants in the transfer of rights to land and buildings in Padang city can be excluded from tax collection by submitting an income tax certificate for inheritance and donations between blood families in a straight line. Constraints in imposing Income Tax on estate and awards in the transfer of rights to land and or buildings in the city of Padang, are still taxpayers who have an NPWP but do not report their annual SPT and there are taxpayers who are not registered at the Tax Office and do not have NPWP, which causes the SKB application to be rejected or not granted.